Risk Factors Associated with the Incidence of Ventricular Arrhythmias Complicating Acute Myocardial Infarction and Prognosis Analysis. (1st June 2021) - Li, Guibin; Liu, Shengxin; Jin, Jiali; Ding, Kejun; Qian, Caizhen
Abstract : Ventricular arrhythmias (VTA) usually occur following acute myocardial infarction (AMI). However, risk factors for VTA attack after AMI have been not well-recognized. The purpose of the study is to identify risk factors associated with the incidence of VTA complicating AMI. A total of 200 patients with AMI who were admitted to our hospital from February 2018 to February 2020 were retrospectively analyzed. These 200 patients were classified into a non-VTA group (n = 140 ) and a VTA group (n = 60 ) based on the occurrence of VTA within 24 after AMI. Patients in the VTA group were older than those in the non-VTA group. The VTA group had more numbers of WBCs and neutrophils than the non-VTA group. The level of serum potassium was lower, but the levels of cTnT and CK-MB were higher in the VTA group than in the non-VTA group. The VTA group presented an increase in proportions of anterior MI, TpTe, and proportions of Killip classification ≥ class II but a decline in LVEF when comparable to the non-VTA group. The two groups were not significantly different concerning other variables including sex, tobacco use, alcohol consumption, diabetes mellitus, hypertension, heart rate, Scr, SUA, BUN, PTL counts, TC, TG, HDL-C, LDL-C, D-dimer, BNP, LVS, LVP, and LVEDd. The levels of hsCRP, endothelin-1, and TNF- α were remarkably higher in the VTA group than in the non-VTA group (P < 0.001 ). Multivariate logistic regression analysis was performed, with clinical variables including age, WBCs, neutrophils, serum potassium, cTnT, CK-MB, hsCRP, endothelin-1, TNF- α, anterior MI, TpTe, proportions of Killip classification ≥ class II, and LVEF as an independent variable and with the occurrence of VTA as a dependent variable. It was revealed that serum potassium, cTnT, CK-MB, hsCRP, endothelin-1, TpTe, proportions of Killip classification ≥ class II, and LVEF were independent risk factors of VTA complicating AMI. Compared with the non-VTA group, the incidence rate of simple left heart failure, total heart failure, stroke, and dyslipidemia in the VTA group was significantly higher than those in the non-VTA group (P < 0.05 ). It was found that the proportion of all-cause deaths within one year outside the hospital was higher in the VAT group than in the non-VAT group (P < 0.05 ). Collectively, the study demonstrates serum potassium, cTnT, CK-MB, hsCRP, endothelin-1, TpTe, proportions of Killip classification ≥ class II, and LVEF were independent risk factors of VTA complicating AMI.